Inhibition effect of calcium hydroxide point and chlorhexidine point on root canal bacteria of necrosis teeth - Andry Leonard Je; Achmad Sudirman; Karlina Samadi (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2006)
Calcium Hydroxide point and Chlorhexidine point are new drugs for eliminating bacteria in the root canal. The points slowly and controly realease Calcium Hydroxide and Chlorhexidine into root canal. The purpose of the study was to determined the effectivity of Calcium hydroxide point (Calcium hydroxide plus point) and Chlorhexidine point in eleminating the root canal bacteria of nescrosis teeth. In this study 14 subjects were divided into 2 groups. The first group was treated with Calcium hydroxide point and the second was treated with Chlorhexidine poin. The bacteriological sampling were measured with spectrofotometry. The Paired T Test analysis (before and after) showed significant difference between the first and second group. The Independent T Test which analysed the effectivity of both groups had not showed significant difference. Although there was no significant difference in statistical test, the result of second group eliminate more bacteria than the first group. The present finding indicated that the use of Chlorhexidine point was better than Calcium hydroxide point in seven days period. The conclusion is Chlorhexidine point and Calcium hydroxide point as root canal medicament effectively eliminate root canal bacteria of necrosis teeth.